2003
DOI: 10.1103/physrevb.67.195204
|View full text |Cite
|
Sign up to set email alerts
|

Saddle point for oxygen reorientation in the vicinity of a silicon vacancy

Abstract: A piezospectroscopic analysis of the vacancy-oxygen complex in silicon has enabled us to demonstrate that this defect in the unstable configuration of the saddle point on the reconfiguration trajectory has a trigonal symmetry. This unstable defect configuration may be considered as the precursor for an oxygen diffusion process where the migrating oxygen atom is accompanied by a vacancy. The trigonal saddle point configuration results in a strong electrical polarization of the pair which can aid the jumping to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…This is in agreement to a general trend observed, for example, in the vacancy-oxygen [17] and the vacancy-oxygen-hydrogen [20] complexes, where it has been found that the reorientation barrier increases when there are more electrons captured by a complex. The re-orientation barriers of vacancy-involving orthorhombic (VO) and pseudo-orthorhombic (VOH) complexes are 0.38 and 0.56 eV, respectively.…”
Section: Article In Presssupporting
confidence: 88%
See 1 more Smart Citation
“…This is in agreement to a general trend observed, for example, in the vacancy-oxygen [17] and the vacancy-oxygen-hydrogen [20] complexes, where it has been found that the reorientation barrier increases when there are more electrons captured by a complex. The re-orientation barriers of vacancy-involving orthorhombic (VO) and pseudo-orthorhombic (VOH) complexes are 0.38 and 0.56 eV, respectively.…”
Section: Article In Presssupporting
confidence: 88%
“…Using high-resolution Laplace DLTS (LDLTS) [16] combined with uniaxial stress we confirm that the structure of this defect is orthorhombic. The influence of uniaxial stress on the ionisation process has been studied for different orientations of the stress in relation to the crystallographic directions and it has been concluded that the effect of stress on the process is rather weak in comparison to that already observed for the case of VO [17], the divacancy (V 2 ) [18], and the carbon-hydrogen pair [19] in the n-type silicon. We also have observed that in our samples the defect re-orientation process apparent as a stress-induced alignment effect only occurs at temperatures higher than 300 K. This is the case for both charge states of the PtH 2 centre and, in this respect, does not agree with the findings reported in Ref.…”
mentioning
confidence: 88%
“…The symmetry of VO has been also confirmed by the DLTS measurements combined with the uniaxial stress [2], and recently by the highresolution Laplace DLTS method [10]. The Laplace DLTS peak splitting pattern for the uniaxial stress applied along the main crystallographic directions agrees with the orthorhombic defect symmetry as found in Ref.…”
Section: 3supporting
confidence: 58%
“…When the defect is in the neutral charge state the effective barrier for reconfiguration of the oxygen atom is 0.38eV [2,9,10]. It has been observed that this barrier is reduced by the stress when the stress is applied along the <100> direction.…”
Section: 3mentioning
confidence: 96%
“…The perturbation of the splitting patterns of the defect is observed after application of stress at elevated temperature. After cooling the stress is removed and the time to return to equilibrium observed as a function of temperature [26,27]. This is potentially an extremely powerful method to study defect motion and predict its significance in device performance and degradation.…”
Section: Radiation Damage In Satellite Cellsmentioning
confidence: 99%